ANALISIS PERSEPSI KEMUDAHAN PENGGUNAAN DAN PERSEPSI KEGUNAAN TERHADAP PENGGUNAAN STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK PADA KOPERASI DI SEMARANG - Imam Setijawan; Rina Permatasari (Jurnal Bisnis dan Ekonomi, 2014)
The purpose of this study was to determine the perceptions that influence the use of SAK ETAP Cooperative in Semarang . In this study analyzed the perceptions of the ease and usability of Financial Accounting Standards Entities Without Public Accountability in Cooperative in Semarang , due to the change in the accounting standard perceptions related to the understanding of the use of financial accounting standards have a very high influence in the adoption of Financial Accounting Standards Entities without Public Accountability. The population in this study are employees and managers Cooperative in Semarang . The population consisted of 100 people . The sample was as much as its population . which amounted to 21 cooperatives . Sources of data and methods of data collection using case studies and census by providing kuosioner to the informant . The analysis in this study using multiple linear regression to determine the effect of each variable. The results of the test with SPSS , using multiple linear regression equation Y = -8.504 + obtained 0.670 X1 - 0.957 X2 + 0.399 X3 + 0.818 X4 - X5 0.062 + ε .Perception variables known tends to be that the stronger the influence of perceptions of readiness it will tend to the higher use of SAK ETAP . Understanding the perception variables, tends to be weakened the influence of perceptual understanding of the information is likely to be increasingly weak use of SAK ETAP . Variable perceived ease of use in mind , tend to that variable perceived ease of use has a positive influence on the use of SAK ETAP . Variables perceived usefulness , usability perception tends to be that the variable has a positive influence on the use of SAK ETAP . Perception variable presentation of financial statements known -0.062 is negative , tends to be that the weaken the influence of the perception of the financial statements will tend to become weaken use of SAK ETAP . Keywords : SAK ETAP , Cooperative , Perception .